التغيرات الهيكلية في بنية الصادرات وأثرها في النمو الاقتصادي في سورية - عثمان, سلمان; صقر, محمد; علي, علاء (Latakia University Journal - Economic and Legal Sciences Series, 2016)
أصبحت قضية الصادرات من القضايا الهامة التي تأتي في سلم أولويات دول العالم لما لها من تأثير مباشر في تحقيق النمو الاقتصادي الذي أصبح من أهم القضايا التي تسعى الدول (المتقدمة والنامية) على حد سواء إلى تحقيقها. عند دراسة واقع الصادرات السورية تبين أنها تعاني من عدة نقاط ضعف تنعكس سلباً على واقع الاقتصاد السوري ، لذا يهدف البحث إلى إيجاد مستوى معين من التغير الهيكلي لتحقيق معدلات نمو في كلٍ من الصادرات والناتج المحلي الإجمالي، وقد تبين أن نمو قطاع الصناعة التحويلية (كأحد مظاهر التغير الهيكلي) له أثر هام وملحوظ في نمو كليهما، إذ إن نمو هذا القطاع خلال الفترة المدروسة بمقدار (1%) سيؤدي إلى نمو الصادرات بمقدار (2.45%) ونمو الناتج المحلي الإجمالي بمقدار (0.44%) في سورية أخيراً توصي الدراسة بضرورة التركيز على قطاع الصناعة التحويلية من خلال إيجاد قاعدة صناعية عريضة بوصفه متطلباً مسبقاً لتنمية الصادرات بشكل خاص ولتحقيق معدلات نمو اقتصادية عالية بشكل عام . Exports have become an issue of significant issues that come in the priority countries of the world because of its direct impact on economic growth, which has become the most important issues, which seeks countries (developed and developing) both to achieve. When studying the reality of Syrian exports show it suffers from several weaknesses reflect negatively on the reality of the Syrian economy, so research aims to find certain level of structural change to achieve the growth rates in both exports and GDP,. has been shown that the growth of the manufacturing sector (as one of the manifestations of structural change) have a significant impact and noticeable growth in both, as the growth of this sector during the period studied by (1%) will lead to the growth of exports by (2.45%) and GDP growth by (0.44%) in Syria. Finally, the study recommends the need to focus on the manufacturing sector through the creation of a broad industrial base as a prerequisite for the growth and development of exports in particular and high Economic Rats in general.